2011
DOI: 10.3109/13880209.2011.559585
|View full text |Cite
|
Sign up to set email alerts
|

Salvianic borneol ester reduces β-amyloid oligomers and prevents cytotoxicity

Abstract: (2011) Salvianic borneol ester reduces β-amyloid oligomers and prevents cytotoxicity, Pharmaceutical Biology, 49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Therefore, it is important to control this nucleated polymerization since it is the rate of aggregation that determines toxicity and neuronal apoptosis in AD. A synthetic compound based on medicinal plant which contains borneol destabilized Aβ oligomers (Han et al, 2011). Thus, natural herbs using the root of Salvia miltiorhiza Bunge (Lamiaceae) (Ren et al, 2004), the whole plant of Ginkgo biloba L. (Ginkgoaceae) (Das et al, 2002) or extracted herbal compounds (Mukherjee et al, 2007;Lin et al, 2008;Guo et al, 2010) can provide the rationale for the pharmacotherapy of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to control this nucleated polymerization since it is the rate of aggregation that determines toxicity and neuronal apoptosis in AD. A synthetic compound based on medicinal plant which contains borneol destabilized Aβ oligomers (Han et al, 2011). Thus, natural herbs using the root of Salvia miltiorhiza Bunge (Lamiaceae) (Ren et al, 2004), the whole plant of Ginkgo biloba L. (Ginkgoaceae) (Das et al, 2002) or extracted herbal compounds (Mukherjee et al, 2007;Lin et al, 2008;Guo et al, 2010) can provide the rationale for the pharmacotherapy of AD.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to promote mental alertness by relieving symptoms of anxiety, fatigue and insomnia (Silva-Filho et al, 2011). Han et al (2011) showed that salvianic borneol ester, synthesized by salvianic acid A and borneol, destabilized β-amyloid (Aβ) peptide aggregates and demonstrated the neuroprotective effects against hydrogen peroxide-induced toxicity in human neuroblastoma cells and motor neuron hybridoma cells. Saravanakumar et al (2012) investigated the protective effect of borneol on liver metabolism in a nitric oxide deficient rat model of hypertension and suggested that borneol had the potential to be used as a novel defense on altered hepatic metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, treatment with isoborneol, a monoterpenoid alcohol, significantly reduced 6-hydroxydopamine-induced ROS generation and cell death in human neuroblastoma SH-SY5Y cells, suggesting that isoborneol may be a potential therapeutic agent for treatment of neurodegenerative diseases associated with oxidative stress (101). Salvianic borneol ester, a new compound synthesized from salvianic acid A and borneol, also exerts anti-amyloid and neuroprotective effects in both SH-SY5Y cells and motor neuron hybridoma VSC 4.1 cells (102). …”
Section: Terpenes and Neuronal Healthmentioning
confidence: 99%
“…These cells were originally designed to elucidate mechanisms of motoneuronal degeneration in amyotropic lateral sclerosis [9,7,10,11,8]; however, they have also been widely investigated following glutamate toxicity [12,13], inflammatory stress [14,15], oxidative stress [14,16], amyloid toxicity [17], copper toxicity [18], and proteolytic activation [19]. Accordingly, these cells were chosen to model EtOH-induced proteolytic damage in mature motoneurons.…”
Section: Introductionmentioning
confidence: 99%